2021
DOI: 10.3389/fendo.2021.777997
|View full text |Cite
|
Sign up to set email alerts
|

Appetite Regulation of TLR4-Induced Inflammatory Signaling

Abstract: Appetite is the basis for obtaining food and maintaining normal metabolism. Toll-like receptor 4 (TLR4) is an important receptor expressed in the brain that induces inflammatory signaling after activation. Inflammation is considered to affect the homeostatic and non-homeostatic systems of appetite, which are dominated by hypothalamic and mesolimbic dopamine signaling. Although the pathological features of many types of inflammation are known, their physiological functions in appetite are largely unknown. This … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(8 citation statements)
references
References 138 publications
(145 reference statements)
1
7
0
Order By: Relevance
“…The balance of α-MSH with other orexigenic peptides has also been investigated, and the serum α-MSH level might be a good biomarker for hypothalamic obesity, as well as for the detection of patients with PCSK1, POMC, and LEPR deficiencies, which may be another breakthrough for the treatment of obesity [[99], [254]]. Additionally, high-fat diet-induced obesity is associated with low-grade inflammation (including IL-1, IL-6, and TNF-α), which changes the levels of neuropeptides, potentially increasing appetite, and weight [[255]]. By downregulating inflammatory factors and changing cell response mechanisms, α-MSH is also an anti-inflammatory hormone that has the potential to treat obesity [[256]].…”
Section: Discussionmentioning
confidence: 99%
“…The balance of α-MSH with other orexigenic peptides has also been investigated, and the serum α-MSH level might be a good biomarker for hypothalamic obesity, as well as for the detection of patients with PCSK1, POMC, and LEPR deficiencies, which may be another breakthrough for the treatment of obesity [[99], [254]]. Additionally, high-fat diet-induced obesity is associated with low-grade inflammation (including IL-1, IL-6, and TNF-α), which changes the levels of neuropeptides, potentially increasing appetite, and weight [[255]]. By downregulating inflammatory factors and changing cell response mechanisms, α-MSH is also an anti-inflammatory hormone that has the potential to treat obesity [[256]].…”
Section: Discussionmentioning
confidence: 99%
“…Toll-like receptor 4, a member of the toll-like receptor family, plays an important role in cellular immunity [55]. Studies have shown that TLR4 is abundantly expressed in microglia and is associated with pathogenesis of neuroinflammation [56].…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, experimental research shows that melatonin upregulates sirtuins, with a consequent downregulation of transcription for pro-inflammatory proteins and kappa-light-chain-enhancer of activated B cells (NF-κB) by suppressing the activation of toll-like receptor 4 (TLR4) and NLRP3 inflammasome [4,69]. TLR4 activation leads to pro-inflammatory signaling (i.e., NF-κB) and synthesis of proinflammatory cytokines [70,71]. NLRP3 inflammasome is a protein complex that assembles in response to cellular stress, promoting inflammation; its chronic aberrant activation is part of the etiopathogenesis of numerous diseases characterized by lowgrade inflammation [72].…”
Section: Cardiovascular Diseasesmentioning
confidence: 99%